Unmanned aerial vehicle localization using distributed sensors - Seung Yeob Nam; Gyanendra Prasad Joshi (International Journal of Distributed Sensor Networks)
The use of unmanned aerial vehicles of varying types and sizes has increased drastically in recent years. Finding the exact geometric location of these unmanned aerial vehicles is important for several reasons. In this work, we investigate a new approach to localizing unmanned aerial vehicles using multiple image sensors, such as cameras connected through sensor networks, so that sensitive areas can be protected. In the proposed approach, image sensors deployed in the ground measure the azimuth angle and angle of elevation of the target vehicle and send that information to a collector node, so it can estimate the location of the target vehicle based on the collected samples. Two estimation methods are proposed to solve the localization problem. The first scheme localizes the projection of the target vehicle on the horizontal plane and estimates the altitude later. The second scheme estimates the location of the target vehicle directly in three-dimensional space. The performance of the proposed schemes is evaluated through simulation.